Thematic Progression in Students’ Descriptive Text - Purba, Grace; Nahum Pasaribu, Arsen (International Journal of Educational Research & Social Sciences, 2021)
A way for developing good writing skills is by using thematic progression. It can help students improve their writing abilities. Theme and rheme are used to analyze the thematic progression. This study aimed to find out the types of thematic progression of students' descriptive texts and the most dominant pattern of thematic progression in students’ descriptive texts. The researcher used the descriptive qualitative method in the research design. There were 50 texts written by students at SMP Swasta Sultan Agung Pematangsiantar. The data was analyzed using (Eggins, 2005) theory as the theoretical framework that found three types of thematic progression. The findings revealed that the students' descriptive texts follow three thematic progression patterns: reiteration or constant pattern, zig-zag or linear pattern, and multiple patterns or split rheme pattern. The constant pattern was the most dominant used by students in 271 occurences (91.80%), followed by zig-zag or linear pattern occurred 13 times (4.4%) and multiple patterns or split rheme pattern occurred 11 times (3.8%)l. The findings show students, in writing descriptive text, tend to use simple thematic progression due to their level of knowledge in grammar and thematic progression is relatively low.